2013
DOI: 10.1186/1742-2094-10-71
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor stimulation increases phagocytosis of Cryptococcus neoformans by microglial cells

Abstract: BackgroundToll-Like receptors (TLRs) belong to the family of pattern-recognition receptors with a crucial function of recognising pathogen-associated molecular patterns (PAMPs). Cryptococcal meningitis is a potentially fatal disease with a high mortality and risk of neurological sequelae.MethodsWe studied the ability of microglial cells to increase the phagocytosis of cryptococci after stimulation with agonists of TLR1/2, TLR3, TLR4 and TLR9.ResultsStimulation of murine microglial cells with these TLR agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
4
54
0
1
Order By: Relevance
“…This is likely due to the poor response of CNS resident cells in recognizing and responding to C. neoformans. The fact that we did not observe full activation of microglia until 21 days postinfection is supported by previous studies showing that C. neoformans can be phagocytosed and induce cytokine and chemokine production by microglia, including CCL3, CCL4, and CCL5, but these effects are severely hindered in the absence of opsonizing antibody or additional stimulatory factors (45,47,50,51,53). Thus, it appears that substantial time is required to overcome the poor activation and impaired phagocytosis of C. neoformans by microglia and to provide significant antigenic stimulation to prompt local reactivation and proliferation of peripherally licensed T cells surveilling the CNS.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This is likely due to the poor response of CNS resident cells in recognizing and responding to C. neoformans. The fact that we did not observe full activation of microglia until 21 days postinfection is supported by previous studies showing that C. neoformans can be phagocytosed and induce cytokine and chemokine production by microglia, including CCL3, CCL4, and CCL5, but these effects are severely hindered in the absence of opsonizing antibody or additional stimulatory factors (45,47,50,51,53). Thus, it appears that substantial time is required to overcome the poor activation and impaired phagocytosis of C. neoformans by microglia and to provide significant antigenic stimulation to prompt local reactivation and proliferation of peripherally licensed T cells surveilling the CNS.…”
Section: Discussionsupporting
confidence: 67%
“…As brain resident macrophages, microglia are among the first cells to encounter C. neoformans during CNS infection and are capable of antimicrobial effector responses (22,45,(50)(51)(52)(53). Thus, we initially anticipated that these cells would become activated in response to C. neoformans within the infected CNS early during infection prior to the accumulation of BIL.…”
Section: Resultsmentioning
confidence: 99%
“…TLR2, TLR4 and TLR9 have been shown to bind and interact with zymosan (yeast β-glucan), GXM and fungal DNA, respectively [6971]. Redlich et al demonstrated that stimulation of microglial cells by these TLR agonists enhanced C. neoformans phagocytosis [72]. …”
Section: Innate Immune and Cellular Responses To C Neoformansmentioning
confidence: 99%
“…Zhao et al [17] and Yan et al [18] have shown that LPS-stimulated human macrophages and dendritic cells preheated to 39.5 o C show an increase in toll like receptor-4 expression. Bearing in mind that TLRs are phagocytosis-promoting factors [15,19], their enhanced expression by elevated temperature may serve as an additional mechanism for heat-stimulated phagocytosis. It is notable that phagocytosis of various pathogens, depends on a relatively large number of factors that either enhance [20][21][22], or reduce this cell activity [23].…”
Section: Discussionmentioning
confidence: 98%